Evaluation of Forage Quality of Oats and Berseem Under Varying Intercropping Row Ratios - Arif, Mohd.; Ravindra Kumar; Arvind Kumar; R. Pourouchottamane; D. L. Gupta; B. Rai (Indian Journal of Animal Nutrition, 2023)
A field experiment was conducted at agriculture farm, ICAR-Central Institute for Research on Goats, Makhdoom, Mathura (Uttar Pradesh) during the rabi season of 2020-21 to study the effect of different intercropping combinations on fodder qualities of oats and berseem. The treatments consist of nine intercropping combinations viz. sole oats, sole berseem, oats + berseem (1:1 row ratio), oats + berseem (2:1 row ratio), oats + berseem (1:2 row ratio), oats + berseem (2:2 row ratio), oats + berseem (3:1 row ratio), oats + berseem (1:3 row ratio), oats + berseem (3:3 row ratio). The experiment was laid out in randomize block design with three replications. The result showed that maximum total dry matter yield of intercropping (8.00 t ha-1) was recorded with 2:1 row ratios of Oats + Berseem intercropping combination. Further, in fodder oats highest value of crude protein (I cut- 12.94%, II cut- 12.17% and III cut- 11.08%), ether extract (I cut- 2.93%, II cut- 2.58% and III cut- 2.05%), TDN content (68.12%), DMI (2.50%), RFV (133.24 %) and NEl (1.63%) were recorded with Oats + Berseem (1:3) intercropping combination, whereas in fodder berseem highest value of crude protein (I cut- 19.12%, II cut- 18.22% and III cut- 16.94%), ether extract (I cut- 3.58%, II cut- 3.39% and III cut- 3.08%), TDN content (64.50%), DMI (2.73%), RFV (141.12%) and NEl (1.55%) were recorded with sole cropping of fodder berseem. However, in berseem 1:3 row ratios of Oats + Berseem intercropping combination recorded at par values of qualities parameter with sole berseem treatment. Thus, Oats + Berseem (1:3) intercropping combination is the best combination for fodder quality improvement of cereal component in cereal + legume intercropping.